2005
DOI: 10.1182/blood-2005-03-1206
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fluid accumulation during stem cell mobilization: a novel prognostic factor of first-year survival after stem cell transplantation in AL amyloidosis patients

Abstract: High-dose melphalan followed by stem cell transplantation (HDM-SCT) has become the treatment of choice for patients with immunoglobulin light chain amyloidosis (AL). Unfortunately, treatment mortality can be excessive in certain subpopulations. We have noted that patients who gained more than 2% body weight during mobilization had a poorer outcome following HDM-SCT. Excluding 2 patients for lack of weight record and denial of consent, 126 patients between July 1997 and June 2003 were retrospectively studied.We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…Among these patients, 52% experienced a weight gain of greater than 2% during mobilization, and the median weight gain during mobilization of all patients exceeded 2.25%. 6 This extent of weight gain was challenging in the cohort of patients, 47% of whom had cardiac amyloidosis. We also demonstrated that diuretic use at baseline and diuretic dose adjustments were more common in patients who gained weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these patients, 52% experienced a weight gain of greater than 2% during mobilization, and the median weight gain during mobilization of all patients exceeded 2.25%. 6 This extent of weight gain was challenging in the cohort of patients, 47% of whom had cardiac amyloidosis. We also demonstrated that diuretic use at baseline and diuretic dose adjustments were more common in patients who gained weight.…”
Section: Discussionmentioning
confidence: 99%
“…5 We have reported that an increase of more than 2% of a patient's body weight during stem cell mobilization resulted in a poor outcome after highdose therapy. 6 A weight increase of more than 2% occurred during mobilization in more than half of the patients. Also, the amyloidosis research group at Boston University has noted that edema is a complicating factor in 23% of patients and pulmonary edema was seen in 18% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…No one was lost to follow-up. Details of the stem cell mobilization and conditioning was described elsewhere [9]. Briefly, growth factor either G-CSF/GM-CSF (5 lg/kg/day) without cyclophosphamide was the standard mobilization regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Significant weight gain during HPC collection has previously been shown to be an independent predictor of mortality post auto-HCT in AL patients. 10 It is important to highlight that our cost analysis does not necessarily reflect the actual reimbursement and institutional overhead associated with mobilization and its complications. Hospital charges and reimbursements vary depending on transplant center's billing practices and the patient's insurance provider (Medicaid vs Medicare vs private insurance).…”
mentioning
confidence: 99%
“…8,9 In addition, significant weight gain and mobilization failure are other important complications with this approach. 10,11 Plerixafor, a selective and reversible antagonist of CXCR-4 (C-X-C a chemokine receptor type 4) has proven efficacy in combination with G-CSF for HPC mobilization, primarily in the context of myeloma and non-Hodgkin lymphoma. 12 We recently reported superior efficacy, significantly less weight gain and no mobilization failures with an upfront plerixafor plus abbreviatedcourse G-CSF (G+P) mobilization approach in AL amyloidosis, compared with a historical control of G-CSF-only group.…”
mentioning
confidence: 99%